2000
DOI: 10.1103/physrevd.62.044045
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic waves in a wormhole geometry

Abstract: We investigate the propagation of electromagnetic waves through a static wormhole. It is shown that the problem can be reduced to a one dimensional Schrödinger-like equation with a barrier-type potential. Using numerical methods, we calculate the transmission coefficient as a function of the energy. We also discuss the polarization of the outgoing radiation due to this gravitational scattering.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Other suggested metrics [31] for generating rotating wormholes, used also in [50,60], failed to generate fluid wormholes [49]. Such metrics, where g φφ (r, θ)/g θθ (r, θ) ≡ sin 2 θ , cannot be brought into the form (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other suggested metrics [31] for generating rotating wormholes, used also in [50,60], failed to generate fluid wormholes [49]. Such metrics, where g φφ (r, θ)/g θθ (r, θ) ≡ sin 2 θ , cannot be brought into the form (13).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the source term for such generated rotating wormholes, found in [31], is not that of a fluid [49,50]. However, the elements of the proof given in [49] rely on the assumption that the fluid undergoes only a rotational motion about a fixed axis. So, it might still be possible to attach a fluid interpretation to the general metric generating rotating wormholes [31] (but not to the specific example of the Teo wormhole [31] as it violates the condition G r θ = 0) if (1) one considers, besides the rotational motion, a radial motion too, and (2) one imposes the condition G r θ = 0, which constrains the components of the Teo general rotating metric.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a given Cartesian coordinate frame with ds 2 = g µν dx µ dx ν , let us define H µν = √ −gF µν and employ the decompositions [9] F µν → (E, B),…”
Section: Maxwell's Equations In a Curved Spacetimementioning
confidence: 99%
“…Also, studying the propagation of different types of perturbations in wormhole geometries was initiated by Kar and Sahdev [8], and Kar et al, who studied the reflection and transmission of massive scalar waves in the presence of an ultrastatic wormhole. Moreover, propagation of electromagnetic waves through a static wormhole is investigated by Bergliaffa and Hibberd [9].…”
Section: Introductionmentioning
confidence: 99%